2016
DOI: 10.25011/cim.v39i1.26325
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of molsidomine against doxorubicin-induced renal damage in rats

Abstract: Purpose: The purpose of this study was to investigate the therapeutic and protective effects of molsidomine (MLS) against doxorubicin (DOX)-induced renal damage in rats.Methods: Forty rats were randomly divided into five groups (control, MLS, DOX, DOX+MLS and MLS+DOX groups). Thiobarbituric acid reactive substance (TBARS), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), nitric oxide (NO) and glutathione peroxidase (GPx) levels were determined from kidney tissues and blood urea nitrogen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In this study, BAs reduced the increased MDA levels and significantly enhanced GSH level in a dosedependent manner versus DXR group. The enhanced GSH level in BAs-treated mice may partially explain its nephroprotective effect as GSH provides a thiol group triggering detoxification processes of glutathione peroxidase [51]. Moreover, co-treatment with BAs diminished peroxidation of lipids in the kidney tissue with significant protection of tubular structures against DXRinduced injury.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, BAs reduced the increased MDA levels and significantly enhanced GSH level in a dosedependent manner versus DXR group. The enhanced GSH level in BAs-treated mice may partially explain its nephroprotective effect as GSH provides a thiol group triggering detoxification processes of glutathione peroxidase [51]. Moreover, co-treatment with BAs diminished peroxidation of lipids in the kidney tissue with significant protection of tubular structures against DXRinduced injury.…”
Section: Discussionmentioning
confidence: 98%
“…MDA content is an important parameter to reflect the potential antioxidant capacity, which can reflect the rate and intensity of lipid peroxidation, and also indirectly reflect the degree of tissue peroxidation damage. This process can induce kidney injury and promote its development (Oguz et al 2016). In order to maintain the stability of the internal environment in animals, a balance between oxidation and antioxidant substances is needed (Olga et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier investigations, we showed that treatment with DOX results in low levels of these enzymes or non-enzymatic antioxidants. Thus, rats treated with DOX exhibited lower levels of SOD and CAT than the untreated controls, according to Oguz et al (2016). In addition, when free radicals grow, SOD and CAT activity, which protect the cell membrane and its contents, decreases significantly and oxidative stress results in low levels of SOD and CAT, increasing the amount of H2O2 in cells (Ighodaro & Akinloye, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, when free radicals grow, SOD and CAT activity, which protect the cell membrane and its contents, decreases significantly and oxidative stress results in low levels of SOD and CAT, increasing the amount of H2O2 in cells (Ighodaro & Akinloye, 2018). Toxins are mostly eliminated and reduced in cells affected by GSH and low levels of GSH weaken the body's ability to fight against ROS (Oguz et al, 2016). It has been hypothesized that there is a relationship between GPx and GSH, because earlier studies have shown that decreased GPx activity could have played a role in determining the availability of GSH in comparison to the DOX-treated group and control groups (Shabalala et al, 2017).…”
Section: Discussionmentioning
confidence: 99%